Growth and puberty in hydrocephalus - (:unkn) unknown (Springer International Publishing, 2019)
Children with hydrocephalus are prone to develop endocrinological problems. Short stature and precocious puberty are the most frequent endocrine sequela of hydrocephalus in children with frequency depending on the associated malformations and medical problems. Short stature is caused by a variety of factors including skeletal abnormalities associated with hydrocephalus, low birth weight, and growth hormone deficiency. Precocious puberty is linked to variations in the intracranial pressure. The effect of shunting on short stature and precocious puberty in hydrocephalic children is not clear, as it can occur before and after shunting and even in arrested hydrocephalus. Timely identification of these problems and referral to pediatric endocrinology is of utmost importance since treatment of these conditions ameliorates sequela associated with them. Careful monitoring of growth and pubertal status should be a routine part of follow-up examination of hydrocephalic children. © Springer Nature Switzerland AG 2019. All rights reserved.
Keywords: Growth; Hydrocephalus; Meningomyelocele; Precocious puberty; Puberty; Short stature; Spina bifida